Inhaler use in chronic obstructive pulmonary disease patients: a meta-analysis† - Zhou Li-Juan; Wen Xian-Xiu; Jiang Rong; Zhou Huang-Yuan; Li Yan; Mao Xiao-Rang; Lan Mei (Sciendo, 2022)
Objective: To evaluate errors in the use of inhalation techniques in patients with chronic obstructive pulmonary disease (COPD), and to provide evidence for improving the effectiveness of drugs.